DAMPAK GENDER, SOURCING CHANNELS, AND PLACEMENT TERHADAP KINERJA KARYAWAN - Mutmainah, Mutmainah; Murseto, Taufik Dian; Rohmatiah, Ahadiati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.09.TAHUN 2020DO - 10.24843/EEB.2020.v09.i09.p04, 2020)
This research purpose to know of affect gender, sourching channels, and placement on employee performance PT BPR Ekadharma Bhinaraharja. The number of respondens were 69 employee of PT BPR Ekadharma Bhinaraharja in Kawedanan Magetan. Sampling technique use sensus sampling. Analysis method in this research use multiple regression analysis with SmartPLS programme. The results show gender not affect on employee performance, Sourcing Channels affect on employee performance, and placement affect on employee performance. This research model is 59,9 percent, as much 40,5 percent formed by others variable.